Educational Assistance in Eradicating Children’s Al-Qur'an Illiteracy - Mhd Alfat Gunawan; Mickail Ginting; Nikene Sampin; Hujratul Fatimah Batubara; Nurul Hidayah (Universitas Pahlawan Tuanku Tambusai, 2022)
Community service is one of the important aspects of the tridharma of higher education. The community service activities practiced by UIN North Sumatra students are community service (PEMA) in semester 4 and real work lectures (KKN) in semester 7. This study aims to describe the form of educational assistance in eradicating illiteracy in the Qur'an in children. in Simpang Empat Village by KKN Group 1 students at UIN North Sumatra Medan. The focus of the discussion is related to the coaching and mentoring efforts carried out by KKN students for 40 children in Simpang Empat Village, Lawe Bulan District, Southeast Aceh Regency. This study uses a qualitative approach with a descriptive study method. The results of this study indicate that the mentoring activities for eradicating illiteracy in the Qur'an in Simpang Empat Village were carried out well, through the stages of mentoring planning, implementation, to monitoring and evaluation of mentoring, with success indicators in the form of graduation for children reading Iqra' volumes 1-6.